TI_GERICHTE 12.2006.147 vom 26. Februar 2008 , Stralcio di causa diventata senza oggetto in seguito a fallimento - TI Tribunale d'appello (2008)
Stralcio di causa diventata senza oggetto in seguito a fallimento